Efektivitas Kartu Kuartet Gizi Seimbang Terhadap Peningkatan Pengetahuan Gizi Seimbang Pada Siswa Sekolah Dasar Di SDN Tasikmadu 1 Kota Malang - Rohmah Fauzia Oktaviani; Agung Kurniawan; Farah Paramita; Septa Katmawanti (Jurnal Ilmu Kesehatan dan Gizi, 2023)
For students in primary schools, there are still numerous nutritional issues to be solved. There has been an increase in the prevalence of overweight and underweight children in the Malang City area, particularly in the Puskesmas Mojolangu working area. One location where these dietary issues occur is SDN Tasikmadu 1. This is a result of the absence of educational resources for understanding balanced nutrition. The goal of this study is to create a balanced nutrition four card instructional media and evaluate its viability and efficacy as a tool for balanced nutrition education. The study follows the define, design, create, and disseminate framework while using a research and development approach. Due diligence was performed by media and material experts utilizing the BNSP evaluation tool with an average score of 87.50%. The effectiveness test was carried out at SDN Tasikmadu 1 on 30 students using pre-test and post-test instruments. Analysis using paired t-test showed that the tool and its accompanying materials were declared "appropriate" and provision of Balanced Nutrition Quartet Card media was effective in increasing students' knowledge, with an average pre-test score of 55.06 and an average post-test score 87.73 and the result of the paired t-test is P=0.000.